On Symbolism in The Great Gatsby - Jiaqi Zhan; Bai Li (Journal of Social Science and Humanities, 2026)
The Great Gatsby employs a distinct style and language to reveal the moral emptiness and hypocrisy hidden beneath the halo of the Jazz Age, as well as to profoundly explore the spiritual essence of the broken American dream through the lens of broken dreams of love and money, which had a significant impact on American society at the time. He is a highly symbolic figure representing the United States in the 1920s, particularly the broken American ideal of unparalleled wealth and material abundance. In addition to its utilitarian relevance, The Great Gatsby has significant artistic value, with symbolism playing a key role throughout the work. Then this paper introduces Fitzgerald's biography, the novel's period background, and the discussion of symbolism, and then this paper specifically analyzes the symbols used in The Great Gatsby and their significance in conveying the theme of the novel. Finally, the paper draws a conclusion, reflecting on the problems of the American dream, and at the same time, linking with the modernization process of China, from which a warning can be obtained.